(untitled) (Plant Tissue Culture and Biotechnology, 2009)
A simple micropropagation method from nodal and shoot tip explants is reported here for Mentha viridis, an economically important medicinal plant. High frequency of microshoots was obtained from these two explants on MS supplemented with various concentrations of BAP (1.0 - 4.0 mg/l) and Kn (1.0 -4.0 mg/l). Maximum number of shoots was obtained from nodal explants in the medium containing 3.0 mg/l BAP. The root induction was carried out by using IBA and IAA (0.5 - 2.0 mg/l). Among these, high frequency of root proliferation was achieved in the medium containing 1.5 mg/l of IBA. The rooted plantlets were hardened and transferred to the field. The survival rate was 90 - 95% after 25 days. Key words: Micropropagation, Mentha viridis, Node, Shoot tip, Multiple shoots D.O.I. 10.3329/ptcb.v18i1.3243 Plant Tissue Cult. & Biotech. 18(1): 1-6, 2008 (June)